2019
DOI: 10.1007/s00038-019-01236-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between health literacy and health outcomes among male young adults: exploring confounding effects using decomposition analysis

Abstract: Objectives Previous studies indicate substantial correlations between low health literacy and poor health outcomes. However, empirical findings remain inconsistent and are theoretically challenging. In this study, we conceptually place health literacy within an established model of health inequality. Studying multiple pathways, we estimate the associations between health literacy and six health outcomes and decompose these associations with health literacy's covariates. Methods Cross-sectional data from the Yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
1
16
2
3
Order By: Relevance
“…In 2019, Rüegg and Abel showed that HL may be associated with many material, psychosocial and health-related factors, and with socioeconomic status. Among the covariates they considered, interest in health topics was included among the best predictors for a good HL level (42). This nding is in accordance with the results we registered among nursing undergraduates.…”
Section: Discussionsupporting
confidence: 85%
“…In 2019, Rüegg and Abel showed that HL may be associated with many material, psychosocial and health-related factors, and with socioeconomic status. Among the covariates they considered, interest in health topics was included among the best predictors for a good HL level (42). This nding is in accordance with the results we registered among nursing undergraduates.…”
Section: Discussionsupporting
confidence: 85%
“…They found that lower health literacy scores were associated with obesity, smoking, and poor self-reported nutrition behaviors [14]. Other reviews have confirmed possible associations between health literacy and different health behaviors in adolescents [15,16], although other determinants, such as psychosocial factors, may also play a large role alongside health literacy for the health outcomes of young adults [17].…”
Section: Introductionmentioning
confidence: 99%
“…Certain segments in Canadian society are similarly disproportionately affected by low health literacy, especially Aboriginal populations, older adults, recent immigrants, people with low levels of education, those with low English/French proficiency, and those on social assistance [18,19]. In context of these inequities and health disparities, health literacy is considered a modifiable and intermediary factor that can be changed by educational means [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%